Separation Axioms in Quadri-Partition Neutrosophic Soft Topological Spaces (European Journal of Pure and Applied Mathematics, 2025)
This study introduces and explores the concepts of separation axioms within the framework of quadri-partitioned neutrosophic soft topological space (QPNSTS). These spaces are an extension of neutrosophic soft topological structures, designed to handle higher levels of uncertainty through quadri-partitioned neutrosophic soft sets (QPNSs). We presented new definitions and properties of -spaces (i = 0, 1, 2, 3, 4) in this extended context, offering detailed criteria that distinguish these separation conditions. Through a series of illustrative examples, we demonstrate how these conditions behave and interact within the structure of QPNSTS. The relationships among these separation axioms, as well as their connections to other results, are also discussed.
Keywords: Neutrosophic soft set, quadri-partitioned neutrosophic soft set, quadri-partitioned neutrosophic soft topological space, quadri-partitioned neutrosophic soft separation axioms.